Chromosome-level genome of Thymus mandschuricus reveals molecular mechanism of aroma compounds biosynthesis - Jia, Lin; Xu, Ning; Xia, Bin; Gao, Wenjie; Meng, Qingran; Li, Qiang; Sun, Ying; Xu, Shoubin; He, Miao; Gu, Huiyan (Frontiers in Plant Science, 2024)
Background: Thymus mandschuricus is an aromatic and medicinal plant with notable antibacterial and antioxidant properties. However, traditional breeding methods rely on phenotypic selection due to a lack of molecular resources. A high-quality reference genome is crucial for marker-assisted breeding, genome editing, and molecular genetics. Results: We utilized PacBio and Hi-C technologies to generate a high-quality chromosome-level reference genome for T. mandschuricus, with a size of 587.05 Mb and an N50 contig size of 8.41 Mb. The assembled genome contained 29,343 predicted protein-coding genes, and evidence of two distinct whole genome duplications in T. mandschuricus was discovered. Comparative genomic analysis revealed rapid evolution of genes involved in phenylpropanoid biosynthesis and the CYP450 gene family in T. mandschuricus. Additionally, we reconstructed the gene families of terpenoid biosynthesis structural genes, such as TPS, BAHD, and CYP, and identified regulatory networks controlling the expression of aroma-synthesis genes by integrating transcriptome data from various organs and developmental stages.We discovered that hormones and transcription factors may collaborate in controlling 2 aroma-synthesis gene expression. Conclusions: This study provides the first high-quality genome sequence and gene annotation for T. mandschuricus, an indigenous thyme species unique to China. The genome assembly and the comprehension of the genetic basis of fragrance synthesis acquired from this research could potentially serve as targets for future breeding programs and functional studies.